EFEKTIFITAS METODE JARIMATIKA DALAM MENINGKATKAN KEMAMPUAN PERKALIAN BAGI ANAK KESULITAN BELAJAR (Single Subject Research di Kelas V SDN 24 Aie Angek Sijunjung) - Sandra - Elita (Universitas Negeri Padang, 2012)
The aim of the research is to improve low student’s multiple ability especially (6-9) by using jarimatika method. The reserch uses single subject research (SSR) with A-B design. The subject is the student who gets difficulties in studying X. The behavior’s target is the student' value in doing the task given. Condition A is Baseline, that is the first condition of student multiple ability before action given. In this baseline condition, he cannot do the task in big numbers (6-9). Condition B, on the other hand, is the intervension, tiven. The technique of the collecting the data is done through written procedure directly. It is made in a form prepared. The the data is formulated in a chart. The result of the research shows that the student’s multiplication ability is increase after using jarimatika method. It can be see from baseline fase (A) is done. The student gets (0) from 20 questions given, after giving intervantion (B). That is teaching multiple by using jarimatika method, student is able to do all 20 questin correctly. So, it can be conclude that jarimatika method is effectife to improve low student’s multiplication ability. Therefore, it is suggested to applly jarimatika method.